Increasing Community Awareness At Medan Aviation Polytechnic Regarding Fire Handling And Safety: Peningkatan Kesadaran Masyarakat di Politeknik Penerbangan Medan Terhadap Penanganan Kebakaran dan Keselamatan - Wardani, Ivana; Nur, Fauziah; Pasa, Inda Tri (Universitas Lancang Kuning, 2025)
Fire represents a serious threat, causing global economic losses estimated at 0.05–0.22% of GDP. In Indonesia, fire incidents remain at a high level, with a total of 267 cases recorded in 2023. Beyond economic losses, fires pose significant risks to human safety, particularly in educational environments equipped with laboratories and dormitories. Common causes of fire risks include electrical short circuits, human negligence, high population density, and limited knowledge of fire protection systems. Politeknik Penerbangan Medan, as a vocational education institution with multi-story buildings and laboratory facilities, faces a considerable potential fire hazard. This Community Service (PkM) program aims to provide fire safety education and fire response training, as well as to equip students with the skills to respond effectively to fire emergencies. The methods implemented include educational outreach, pre-tests and post-tests, and hands-on demonstrations on the use of Light Fire Extinguishers (APAR) and fire blankets. A total of 36 students participated in the entire activity. The evaluation results indicated a 58% increase in knowledge, with the average pre-test score of 67 and post-test score of 78, demonstrating a significant improvement in understanding after the training. The average score increase of 11 points further highlights the program’s effectiveness in enhancing participants’ knowledge. Additionally, participants achieved a 93.5% success rate in basic fire extinguishing skills, reflecting their improved preparedness in handling fire risks. Participant satisfaction assessments showed that conducting this activity as an extracurricular program contributed to fostering a safety-conscious culture within the campus environment and served as a model for sustainable fire safety training.